The great trilemma: are globalization, democracy, and sovereignty compatible?. Issue 2 (17th May 2016) - Stein, Arthur A.
Abstract : Current economic and political developments spotlight the relationship between domestic and global governance and the impact of globalization on both. A key question is whether a sovereign state system, democratic governments, and an integrated global marketplace can coexist. The paper assesses analytic materialist arguments for their incompatibility and the key assumptions on which they rest. The paper describes the extant pressures operating to limit each of the three: how sovereignty and democracy work to constrain globalization, how globalization and sovereignty generate a democratic deficit, and how globalization and democracy lead to limitations upon, and even the transcendence of, sovereignty. How to make the three compatible, and failing that, which facet to restrain, characterizes political contestation in a globalizing age. Global and domestic governance reflect the need to reconcile the combined implications of globalization, sovereignty, and democracy, and to do so by restraining, limiting, or transforming one or more of these features.